Loss of biodiversity : problems of its legal control in Ethiopia - Damtie, Mellese (2014)
This thesis is conducted on the premise that the existing legal, policy and governance frameworks are insufficient to protect biodiversity from the alarming loss it is facing now. It argues that these frameworks are crafted to conform to the dominant paradigm of anthropocentrism; a paradigm which believes that humans are the pinnacle of creation and everything on Earth, including the Earth itself destined to satisfy only the interests of humanity without having their own purpose. By showing how anthropocentric worldview conceived, developed and spread, and how this worldview managed to influence societal collective consciousness to govern the relationship established between humans and the nonhuman nature, the thesis argues that loss of biodiversity not a problem in itself. Rather it is a symptom of the underlying problem rooted in human thinking, guided by anthropocentric worldview. Anthropocentrism has become a powerful paradigm that succeeded in permeating into dominant religions, knowledge base and legal systems of countries of the world, including Ethiopia. The thesis contends that law, as mirror of dominant paradigms and perceptions, reflects the values of these paradigms, at international as well as national levels putting protection of biodiversity within the interpretations of these paradigms. It argues that the human treatment of the natural environment is on a scale of violence which puts the survival of humans and that of the environment at a precarious condition. Based on evidence from the review of evolutionary science and the Holy Scriptures, the thesis argues that humans are deeply connected to and dependent on the Earth systems and are responsible to maintain these systems which are functioning in a holistic manner to support all life on Earth. Promoting the proposition of Thomas Berry that the Earth is a community of subjects not a collection of objects, it contends that biodiversity has intrinsic value in addition to instrumental value, deserving ethical extension. Drawing on these concepts, the thesis suggests, by adopting a reformist approach, a shift from the reductionist notion of anthropocentrism to ecocentrism via the new philosophy called Earth jurisprudence. Earth jurisprudence is believed to correct and heal the conflicting relationship that humans established with the nonhuman nature, with the view to reconciling the present legal, policy and governance systems which have been dominated by anthropocentric perspectives. Through the vehicle of Earth jurisprudence, it is hoped that humans assume a stewardship responsibility for the mutual benefits of humans and nonhuman nature. The thesis finally deals with a case study conducted in Sheka zone in the Southwest Ethiopia. The case study is done with the purpose of exploring the TEG systems of indigenous/local communities which are believed to conform to the tenets of the Earth jurisprudence, the philosophy of law which is chosen by this work to guide the protection of biodiversity. The case study came out with findings that the Sheka TEG systems are good examples of customary practices that provide better protection for biodiversity. Exemplary lessons can be drawn from the Sheka TEG systems to amend the dominant legal, policy and governance regimes.